Gambaran Kesehatan Mental Siswa Pada SMP Negeri X di Halmahera Tengah - Annisa Isma Ramadhona; Anniez Rachmawati Musslifah; Sri Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Adolescent mental health is a fundamental aspect in supporting the academic, social, and emotional development of junior high school students. This study aims to describe in depth the mental health conditions of students at SMP Negeri X in Central Halmahera Regency, located in the 3T (underdeveloped, frontier, and outermost) region. The focus of the study includes students' understanding of mental health, emotional regulation skills, awareness of seeking help, empathy and social interaction, as well as teachers' views and roles in supporting students' mental health. The study used a descriptive qualitative approach with a phenomenological method. The research subjects consisted of six students and three teachers selected purposively. Data collection techniques included in-depth interviews, observation, and supporting documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that students have a basic understanding of mental health, but it is still limited and tends to simplify the concept of mental health as the absence of stress or severe disorders. Students' emotional regulation abilities are in the developing stage, with a combination of adaptive and maladaptive coping strategies. Awareness of seeking help is still low, indicated by students' tendency to prefer peers over adults. Social interaction and empathy are relatively positive, although stigma against emotional expression is still found. Teachers recognize the importance of student mental health, but face limitations in competency, facilities, and policy support. This study concludes that strengthening mental health literacy, increasing teacher capacity, and developing sustainable and contextual school support systems in the 3T (United Nations, 3T) regions is necessary.